1718. Rezafungin Clinical Safety and Efficacy in Patients With Candidemia and/or Invasive Candidiasis in the Randomized, Double-Blind, Multicenter, Phase 2 STRIVE Study. (26th November 2018) - Thompson, George R; Vazquez, Jose; Soriano, Alex; Skoutelis, Athanasios; Ostrosky-Zeichner, Luis; Mena, Karen; Navalta, Laura; Sandison, Taylor; Pappas, Peter
Abstract: Background: STRIVE was conducted to assess the safety and efficacy of rezafungin (RZF), a novel echinocandin with pharmacokinetics allowing once weekly dosing and high, front-loaded plasma drug exposure, and to help determine dosing for a Phase 3 study. Methods: Adults (≥18 years) with mycologically confirmed candidemia and/or invasive candidiasis (IC) were randomized (1:1:1) to receive RZF IV for up to 4 weeks dosed at either 400 mg weekly (Group 1) or 400 mg on week 1 and 200 mg weekly thereafter (Group 2), or standard of care (SOC; daily caspofungin [CSP] with optional criteria-defined oral stepdown after ≥3 days of IV therapy; Group 3). Safety and efficacy were evaluated by treatment-emergent adverse events (TEAEs) and overall success at day 14 (1° endpoint; clinical cure + mycological success), investigator assessment of clinical cure, mycological success (in subjects with candidemia only), overall success in IC subjects only, and mortality. Outcomes at day 5 were also assessed. Results: The rate of TEAEs was 88.6% in Group 1, 94.4% in Group 2, and 81.8% in Group 3. Severe AEs occurred in 37.1%, 27.8%, and 39.4% of the groups, respectively. There were no concerning trends in System Organ Class groups, specific AEs, or laboratory abnormalities. The most common Candida species isolated was C. albicans ( n = 45), followed by C. glabrata ( n = 17), C. tropicalis ( n = 15), and C. parapsilosis ( n = 13). A high number of indeterminate responses due to missing data points in Group 1 led to analyses including and excluding the indeterminate responses. Overall, clinical, and mycological response rates at day 14 are shown in Table 1. Overall response at day 5 (Table 2) was highest in the RZF 400 mg/200 mg group, followed by the RZF 400 mg/400 mg and SOC groups. The overall mortality rate was 15.2% in Group 1, 9.7% in Group 2, and 17.9% in Group 3. Conclusion: RZF demonstrated safety and efficacy comparable to CSP in the treatment of candidemia/IC. There were no concerning trends in AEs. The efficacy rates were similar among all 3 treatment groups, trending higher with the RZF 400 mg/200 mg regimen on most efficacy outcomes, although the sample size is small and confirmation of these findings is required in a larger Phase 3 clinical trial. These findings support further clinical study of RZF in Phase 3. Disclosures: G. R. Thompson, Cidara: Investigator, Research support. Mayne: Investigator, Research support. Astellas: Consultant and Investigator, Consulting fee and Research support. Scynexis: Investigator, Research support. Vical: Consultant, Consulting fee. A. Soriano, Cidara Therapeutics, Inc.: Investigator, Research grant. L. Ostrosky-Zeichner, Cidara Therapeutics: Grant Investigator, Research grant. K. Mena, Cidara Therapeutics: Employee, Salary. L. Navalta, Cidara Therapeutics, Inc.: Employee, Salary. T. Sandison, Cidara Therapeutics: Employee, Salary. P. Pappas, Cidara Therapeutics: Consultant and Grant Investigator, Research grant. IMMY: Consultant and Grant Investigator, Research grant. Scynexis: Consultant and Grant Investigator, Research grant. Gilead: Grant Investigator, Research grant.